MATHEMATICAL MODELING AND SIMULATION OF SOCIAL MEDIA ADDICTION TIKTOK USING SEI1I2R TYPE MODEL - Maria Magdalena Abi; Elinora Naikteas Bano; Leonardus Frengky Obe; Fried Markus Allung Blegur (JURNAL DIFERENSIAL, 2023)
TikTok is an entertainment application that can be used to watch and share various short videos such as educational information, dance, fashion, and even promote a product, as well as shop online. If it is used continously, it may provide negative impact. TikTok users may become stressed if it does not meet the creator’s expectations such as getting the most likes or viewers from users. Furthermore, they also can addicted to online shopping and buy something that they do not need due to lost self-control and be unable to consider risks in making decisions resulting in stress or depression. This study aims to build a mathematical model of TikTok addiction Type SEI1I2R. The results of the study obtained two equilibrium points, namely the free equilibrium point for TikTok addiction T1 and be stable when R0 < 1 and the equilibrium point for addiction to TikTok T2 and be stable when R0 > 1. The simulation shows that when R0 <1, even though most of the population have TikTok application, they are not interested in content and shopping via TikTok. This causes the population that creates TikTok accounts decrease and hence the addiction to content and shopping on TikTok slowly decrease and then disappear in the population. Meanwhile, when R0 > 1, many people think that content and shopping on TikTok are very interesting so that the population that creates TikTok accounts is increasing so that there is an increase in the population creating content and shopping on TikTok. Therefore, TikTok addiction will remain in the population and will increase with time.